Ameliorating acute kidney injury following cardiac surgery: do high dose perioperative statins play a role? - Ngu, Janet M. C.; Boodhwani, Munir (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Acute kidney injury (AKI) is relatively common in the patients undergoing cardiac surgery. Over the past decade, several consensus definitions (namely the RIFLE, AKIN and KIDGO) have been developed to provide uniform criteria for the diagnosis of AKI, in order to facilitate comparisons between studies and the development of quantitative research (1-3). The incidence of AKI after cardiac surgery differs slightly depending on the classification criteria, ranging from 31–46% (3-5). It is well known that patients who developed AKI after cardiac surgery are at an increased risk of short-term and long-term morbidity and mortality. These patients tend to have higher mortality rates, prolonged ICU and hospital stay (5-7). These patients also have an increased risk of subsequent developing chronic kidney disease (CKD), which is associated with a higher long-term mortality (8).